Performance of small reservoir irrigation schemes in the Upper East Region - Sekyi-Annan, Ephraim (2015)
Thesis submitted to the Department of Civil Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science in Water Resources Engineering and Management, 2010